A modified reinforced composite fiber material for fracturing and preparation method thereof

By hyperbranching modification of bio-based cellulose and introducing cationic ammonium ions, the problem of insufficient performance of traditional fracturing fiber materials in high-temperature and high-pressure environments is solved, and the comprehensive performance and economic improvement of fracturing fluid are achieved.

CN119219796BActive Publication Date: 2025-03-04XIAN JUNDE PETROLEUM ENG TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411731308.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The existing fracturing fiber materials have insufficient mechanical properties, poor chemical resistance, poor dispersion and constructionability in high-temperature and high pressure environments, and have high cost, which limits the economicality of their large-scale application.

Method used

The bio-based cellulose is hyperbranched by polyamine polymerization and diallyl dimethyl ammonium chloride is introduced to improve cross-linking complexity, while cationic ammonium ions are introduced into the composite fiber material, enhancing its thickening ability and salt resistance in the fracturing fluid.

Benefits of technology

It improves the comprehensive performance of fracturing fluid, including thickening capacity, conveying capacity and sand carrying capacity, extends the service life of fiber materials, reduces production costs, and adapts to high mineralization conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219796B_ABST
    Figure CN119219796B_ABST
Patent Text Reader

Abstract

The invention discloses a modified reinforced composite fiber material for fracturing in the technical field of petroleum extraction and a preparation method thereof. The invention performs hyperbranching modification on bio-based cellulose through polyamine polymerization reaction, adopts diallyldimethylammonium chloride to further improve the cross-linking complexity of bio-cellulose, and introduces cationic ammonium ions into the composite fiber material at the same time, thereby improving the thickening ability in the fracturing fluid, optimizing the conveying ability and sand carrying ability of the liquid in the cracks, and the introduction of cationic groups can improve the salt and alkali resistance of the fracturing fluid, thereby improving the comprehensive performance of the fracturing fluid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum extraction, and specifically refers to a modified reinforced composite fiber material for fracturing and a preparation method thereof. Background Art

[0002] Fracturing technology is a widely used means of increasing production in the process of oil and gas extraction. It forms cracks by injecting high-pressure fluids into the formation, thereby improving the permeability of oil and gas. However, the proppants and fiber materials used in the fracturing process will directly affect the formation of cracks, the support effect and the construction efficiency. Therefore, it is of great significance to study and improve fracturing materials. During the fracturing process, the fracturing fluid (usually a liquid containing water, sand or proppants) is injected into the underground high-pressure well. The purpose is to form cracks by cracking the underground rock formation, thereby releasing oil and gas. The effective support of the cracks is crucial, because if the cracks are not sufficiently supported, they may close again, affecting the flow of oil and gas. Therefore, the commonly used fracturing proppants (also called supporting materials) include: Sand: the most traditional proppant, economical and easy to obtain, but not strong enough under high pressure and high temperature environment, and easy to be compacted; Ceramsite: has good strength and pressure resistance, but has a high density and high cost; Fiber materials: such as glass fiber, carbon fiber, aramid fiber, etc., have light weight and strong support capacity; However, traditional fiber materials still have some obvious shortcomings in application. Traditional fracturing fiber materials are mainly used to prevent crack closure and improve the conductivity of cracks, but there are the following problems in practical applications: Insufficient mechanical properties: Traditional fiber materials such as glass fiber and carbon fiber are prone to lose strength or deform in high temperature and high pressure environments, making it difficult to maintain effective support for cracks for a long time; Poor chemical resistance: Fracturing fluid contains a variety of chemical components, and ordinary fibers may be corroded due to insufficient chemical resistance, affecting their service life; Poor dispersibility and workability: Fiber materials are easy to agglomerate in fracturing fluids, which not only reduces the conductivity, but also may cause pipeline blockage and other construction problems; High cost: Some high-performance fibers (such as aramid fibers) have high manufacturing costs and poor economic efficiency in large-scale applications. The development of fiber materials is mainly aimed at the following problems: Performance degradation in high temperature and high pressure environments: In fracturing operations, the temperature and pressure of the formation are extremely high, which poses a severe challenge to traditional fiber materials (such as glass fiber and polypropylene fiber). The strength of the material will decrease with the increase of temperature, resulting in a weakening of the crack support effect; poor chemical corrosion resistance: fracturing fluid usually contains acidic, alkaline or saline substances, these chemical components will corrode traditional fiber materials and shorten their service life; poor dispersion and construction problems: fiber materials are prone to agglomeration in the liquid, affecting their uniform distribution, resulting in some areas not being able to get enough support, and may also cause problems such as pumping difficulties and pipeline blockages; cost issues: high-performance fiber materials (such as aramid fibers) have excellent mechanical properties, but the production cost is relatively high, which limits the economic feasibility of their large-scale application. Summary of the invention

[0003] In view of the above situation, in order to overcome the defects of the prior art, the present invention provides a modified reinforced composite fiber material for fracturing and a preparation method thereof. In order to solve the problems in the prior art, the present invention hyperbranched the bio-based cellulose through a polyamine polymerization reaction, and used diallyldimethylammonium chloride to further increase the cross-linking complexity of the bio-cellulose. At the same time, cationic ammonium ions are introduced into the composite fiber material, which can improve the thickening ability of the fracturing fluid, optimize the transport capacity and sand carrying capacity of the liquid in the cracks, and the introduction of cationic groups can improve the salt resistance of the fracturing fluid, thereby improving the comprehensive performance of the fracturing fluid.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0005] A method for preparing a modified reinforced composite fiber material for fracturing, specifically comprising the following steps:

[0006] S1. Place the biostraw in an oven, dry at 40°C to constant weight, place in a steel mill to crush, pass through a 200-mesh sieve, soak in deionized water, raise the temperature to 60-70°C, stir at 300-350rpm for 2-3h, place in an oven at 60°C to dry to constant weight, and obtain pretreated biostraw powder;

[0007] Preferably, in step S1, the biological straw includes at least one of wheat straw, corn straw, sorghum straw, rape straw, and sesame straw;

[0008] S2, placing the pretreated bio-straw powder prepared in step S1 in a NaOH aqueous solution, transferring it to a microwave reactor, adjusting the microwave power to 300-400 W, adjusting the temperature to 100-110° C., adjusting the stirring speed to 200-250 rpm, and the reaction time to 15-25 min. After the reaction is completed, cooling, washing with a rinsing solution until neutral, placing it in an oven and drying it at 40° C. to constant weight, to obtain bio-cellulose;

[0009] Preferably, in step S2, the mass concentration of the pretreated bio-straw powder in the NaOH aqueous solution is 10-20 g / L;

[0010] Preferably, in step S2, the mass fraction of NaOH in the NaOH aqueous solution in deionized water is 10%-20%;

[0011] Preferably, in step S2, the bleaching solution is NaClO 2 and acetic acid in aqueous solution, wherein NaClO 2The concentration in deionized water is 35-40g / L; the volume fraction of acetic acid in deionized water is 2%-4%;

[0012] S3, dissolving γ-(2,3-epoxypropoxy)propyltrimethoxysilane in an ethanol aqueous solution, adjusting the pH to 4-4.5, adding the biocellulose prepared in step S2, placing at room temperature, stirring at 250 rpm for 20-24 hours, centrifuging at 5000 rpm for 10-20 minutes, removing the supernatant, washing the precipitate with anhydrous ethanol, and vacuum drying to obtain modified biocellulose;

[0013] Preferably, in step S3, the volume fraction of the γ-(2,3-epoxypropoxy)propyltrimethoxysilane in the ethanol aqueous solution is 5%-10%;

[0014] Preferably, in step S3, the mass volume ratio between the biocellulose and γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 0.25-0.5 g / mL;

[0015] S4, dispersing the modified biocellulose prepared in step S3 in a 50% methanol aqueous solution by volume, mixing until uniformly dispersed, adjusting the pH to 9-9.5, raising the reaction temperature to 70-90°C, and after the temperature of the reaction system is uniform, adding tetraethylenepentamine dropwise, stirring at a speed of 200 rpm during the reaction, and reacting for 4-6 hours, stopping heating, and after the reaction temperature is cooled to room temperature, adding methyl acrylate, continuing to stir the reaction for 10-14 hours, adding ethylenediamine for end-capping, vacuum drying, removing the solvent and excess reactants, and removing the solvent and excess reactants to obtain polyamined biocellulose;

[0016] Preferably, in step S4, the mass concentration of the modified biocellulose in the methanol aqueous solution is 10-20 g / L;

[0017] Preferably, in step S4, the mass volume ratio between the modified biocellulose and tetraethylenepentamine is 2-4 g / mL;

[0018] Preferably, in step S4, the volume ratio between tetraethylenepentamine and methyl acrylate is 1:2-4;

[0019] Preferably, in step S4, the volume ratio between the added volume of ethylenediamine and tetraethylenepentamine is 1.5-2:1;

[0020] S5, dissolving the polyamined biocellulose prepared in step S4 in DMF, introducing flowing nitrogen, adding potassium persulfate, adding diallyldimethylammonium chloride, heating in a water bath to 70-80°C for reaction for 5-7h, cooling after the reaction, adding anhydrous ethanol for precipitation, centrifuging at 4000-5000 rpm for 3-5min, collecting the precipitate, washing with anhydrous ethanol, and drying in a vacuum drying oven at 40°C to obtain a modified reinforced composite fiber material;

[0021] Preferably, in step S5, the mass concentration of the polyaminated biocellulose in DMF is 40-50 g / L;

[0022] Preferably, in step S5, the mass ratio between the potassium persulfate and the polyaminated biocellulose is 1-2:1;

[0023] Preferably, in step S5, the mass ratio between the polyaminated biocellulose and diallyldimethylammonium chloride is 1:3-4.

[0024] The present invention also provides a modified reinforced composite fiber material for fracturing prepared according to the method.

[0025] The beneficial effects achieved by the present invention are as follows:

[0026] The invention provides a modified reinforced composite fiber material for fracturing and a preparation method thereof. The invention uses a polyamine polymerization reaction to perform hyperbranching modification on bio-based cellulose, adopts diallyldimethylammonium chloride to further improve the crosslinking complexity of bio-cellulose, and introduces cationic ammonium ions into the composite fiber material at the same time, thereby improving the thickening ability in the fracturing fluid, optimizing the conveying ability and sand carrying ability of the liquid in the cracks, and the introduction of cationic groups can improve the salt and alkali resistance of the fracturing fluid, thereby improving the comprehensive performance of the fracturing fluid. The invention uses bio-based cellulose as a basic material, which has the characteristics of being renewable and biodegradable, and uses γ-(2,3-epoxypropoxy)propyltrimethoxysilane to perform surface modification on the bio-cellulose, introduces epoxy groups into the surface of the bio-cellulose, and reacts with tetraethylenepentamine through an amine-induced epoxy ring-opening reaction, so that the tetraethylenepentamine is connected to the surface of the bio-cellulose, and methyl acrylate is used to cause the tetraethylenepentamine to undergo a hyperbranching reaction to form a hyperbranched polymer with a polyamine structure, and reacts with the bio-cellulose macromolecule The chain structure forms a complex three-dimensional network structure, and a large number of active amino groups are introduced into the biocellulose macromolecular polymer, which can improve the swelling ability of cellulose in water-based drilling fluid and show excellent thickening performance in fracturing fluid. Diallyl dimethyl ammonium chloride is introduced into the polyamined biocellulose prepared by the present invention, and both ends of the diallyl dimethyl ammonium chloride molecular chain have double bond structures. The double bond groups can undergo cross-linking reactions with the amine groups in the polyamined biocellulose, further improving the complexity of the cross-linking structure of the hyperbranched polymer. At the same time, cationic quaternary ammonium salt groups can be introduced into the cellulose molecules, which can give the biocellulose strong cationic properties and enhance its dispersibility in water. At the same time, the interaction between cellulose and negatively charged particles in the fracturing fluid is improved. The cationic groups can effectively neutralize anions in the salt solution, improve the salt resistance of the fracturing fluid, and adapt to high mineralization conditions. Cationic ammonium ions interact with rock surfaces or negatively charged particles, reduce the adsorption loss of cellulose on the crack surface, and improve its performance utilization efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is an infrared spectrum image of the composite fiber material prepared in Example 1 of the present invention;

[0028] Figure 2 This is a SEM image of the composite fiber material prepared in Example 1 of the present invention;

[0029] Figure 3 The steady-state rheological properties of the water-based drilling fluid made of the composite fiber material described in Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in the figure;

[0030] Figure 4 This is a graph showing the salt resistance filtration loss results of the composite fiber materials prepared in Examples 1-3 and Comparative Examples 1-3.

[0031] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0034] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials and test strains used in the following examples are purchased from commercial channels unless otherwise specified.

[0035] Example 1

[0036] The present invention provides a method for preparing a modified reinforced composite fiber material for fracturing, which specifically comprises the following steps:

[0037] S1. Collect wheat straw, cut it into 5 cm small segments, place it in an oven, set the temperature to 40°C for drying, take out the wheat straw after drying to constant weight, crush it with a steel grinder, pass it through a 200-mesh sieve to obtain wheat straw powder, add deionized water to the wheat straw powder at a solid-liquid ratio of 10 g / L, increase the temperature to 70°C, stir at 300 rpm for 3 hours, pour out the deionized water and floating impurities, place the wheat straw powder in a 60°C oven and dry it to constant weight to obtain pre-treated wheat straw powder;

[0038] S2. Accurately weigh 10 g of the pretreated wheat straw powder prepared in step S1 and place it in a reactor. Prepare 500 mL of a 10% NaOH aqueous solution and add it to the reactor. After mixing evenly, transfer the reactor to a microwave reactor, adjust the microwave power to 300 W, adjust the temperature to 100 ° C, and adjust the stirring speed to 200 rpm. When the temperature rises to 100 ° C, keep the reaction warm for 25 minutes, wait for the reaction system to cool to room temperature, obtain the alkali-treated reactant, and set it aside. Accurately weigh NaClO 240g was dissolved in 1L of deionized water, and 20mL of acetic acid was added to mix and prepare a bleaching solution. The alkali-treated reactant was washed with the bleaching solution until it was neutral, and then filtered. The precipitate was placed in an oven and dried at 40°C to constant weight to obtain wheat cellulose;

[0039] S3, accurately weigh 10 mL of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dissolve it in 200 mL of 85 vol% ethanol aqueous solution, add glacial acetic acid to adjust the pH of the solution to 4.0, stir it at 200 rpm for 2 hours, add 5 g of wheat cellulose prepared in step S2 to the solution, stir it at 250 rpm for 24 hours at room temperature, centrifuge it at 5000 rpm for 10 minutes, remove the supernatant, wash the precipitate repeatedly with anhydrous ethanol to remove unreacted γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and dry it in vacuo at 60°C for 12 hours to obtain modified wheat cellulose;

[0040] S4, accurately weigh 2 g of the modified wheat cellulose prepared in step S3, add 200 mL, 50 vol% methanol aqueous solution, mix well, adjust the solution pH to 9.0, increase the reaction temperature to 90°C, place on a magnetic stirrer and stir thoroughly at 200 rpm, after the temperature of the reaction system is uniform, add 1 mL of tetraethylene pentamine dropwise, continue stirring and reacting for 5 hours, stop heating, after the reaction system is cooled to room temperature, add 2 mL of methyl acrylate, continue stirring and reacting for 12 hours, continue to add 2 mL of ethylenediamine and stir and react for 1 hour, perform end-capping, remove the reaction solvent and excess reactants by vacuum distillation, wash repeatedly with deionized water and anhydrous ethanol, and vacuum dry at 50°C for 8 hours to obtain polyamined biocellulose;

[0041] S5. Accurately weigh 1 g of the polyamined wheat cellulose prepared in step S4, add 20 mL of DMF solvent to fully dissolve the polyamined wheat cellulose, introduce flowing nitrogen into the reaction system, add 2 g of potassium persulfate to fully dissolve it in the reaction system, add 6.15 mL of diallyldimethylammonium chloride aqueous solution (65 wt%, brand Merck Bio, item number 348279), raise the reaction temperature to 70°C, react for 6 hours, wait for the reaction to cool to room temperature, precipitate with 100 mL of anhydrous ethanol, centrifuge at 4500 rpm for 3 minutes, collect the precipitate, wash it alternately with anhydrous ethanol and deionized water for 3 times, and dry it in a vacuum drying oven at 40°C for 5 hours to obtain a modified reinforced composite fiber material;

[0042] The present invention also provides a modified reinforced composite fiber material for fracturing prepared according to the preparation method.

[0043] Example 2

[0044] The present invention provides a method for preparing a modified reinforced composite fiber material for fracturing, which specifically comprises the following steps:

[0045] S1. Collect corn stalks, cut them into 5 cm small segments, place them in an oven, set the temperature to 40°C for drying, and after drying to constant weight, take out the wheat straw, crush it with a steel grinder, and pass it through a 200-mesh sieve to obtain wheat straw powder. Add deionized water to the wheat straw powder at a solid-liquid ratio of 10 g / L, increase the temperature to 60°C, stir at 350 rpm for 2 hours, pour out the deionized water and floating impurities, and place the wheat straw powder in a 60°C oven to dry to constant weight to obtain pre-treated wheat straw powder;

[0046] S2. Accurately weigh 10 g of the pretreated wheat straw powder prepared in step S1 and place it in a reactor. Prepare 1 L of a 20% NaOH aqueous solution and add it to the reactor. After mixing evenly, transfer the reactor to a microwave reactor, adjust the microwave power to 350 W, adjust the temperature to 100 ° C, and adjust the stirring speed to 230 rpm. When the temperature rises to 100 ° C, keep the reaction warm for 20 minutes, wait for the reaction system to cool to room temperature, obtain the alkali-treated reactant, and set it aside. Accurately weigh NaClO 2 35g was dissolved in 1L deionized water, 30mL acetic acid was added, and the mixture was mixed to prepare a bleaching solution. The alkali-treated reactant was washed with the bleaching solution until it was neutral, and then filtered. The precipitate was placed in an oven and dried at 40°C to constant weight to obtain wheat cellulose;

[0047] S3, accurately weigh 20 mL of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dissolve it in 200 mL of 85 vol% ethanol aqueous solution, add glacial acetic acid to adjust the pH of the solution to 4.5, stir it at 250 rpm for 2 hours, add 5 g of wheat cellulose prepared in step S2 to the solution, stir it at 250 rpm for 20 hours at room temperature, centrifuge it at 5000 rpm for 20 minutes, remove the supernatant, wash the precipitate repeatedly with anhydrous ethanol to remove unreacted γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and dry it in vacuo at 60°C for 12 hours to obtain modified wheat cellulose;

[0048] S4, accurately weigh 4 g of the modified wheat cellulose prepared in step S3, add 200 mL, 50 vol% methanol aqueous solution, mix well, adjust the solution pH to 9.5, increase the reaction temperature to 80°C, place on a magnetic stirrer and stir thoroughly at 200 rpm, after the temperature of the reaction system is uniform, add 1 mL of tetraethylene pentamine dropwise, continue stirring and reacting for 4 hours, stop heating, after the reaction system is cooled to room temperature, add 3 mL of methyl acrylate, continue stirring and reacting for 10 hours, continue to add 1.5 mL of ethylenediamine and stir and react for 1 hour, perform end-capping, remove the reaction solvent and excess reactants by vacuum distillation, wash repeatedly with deionized water and anhydrous ethanol, and vacuum dry at 50°C for 8 hours to obtain polyamined biocellulose;

[0049] S5. Accurately weigh 1 g of the polyamined wheat cellulose prepared in step S4, add 25 mL of DMF solvent to fully dissolve the polyamined wheat cellulose, introduce flowing nitrogen into the reaction system, add 1.5 g of potassium persulfate to fully dissolve it in the reaction system, add 4.61 mL of diallyldimethylammonium chloride aqueous solution (65 wt%), raise the reaction temperature to 80°C, react for 5 h, wait for the reaction to cool to room temperature, precipitate with 100 mL of anhydrous ethanol, centrifuge at 5000 rpm for 4 min, collect the precipitate, wash it alternately with anhydrous ethanol and deionized water for 3 times, and dry it in a vacuum drying oven at 40°C for 5 h to obtain a modified reinforced composite fiber material;

[0050] The present invention also provides a modified reinforced composite fiber material for fracturing prepared according to the preparation method.

[0051] Example 3

[0052] The present invention provides a method for preparing a modified reinforced composite fiber material for fracturing, which specifically comprises the following steps:

[0053] S1. Collect rape straw, cut it into 5 cm small segments, place it in an oven, set the temperature to 40 ° C for drying, and after drying to constant weight, take out the rape straw, crush it with a steel grinder, and pass it through a 200-mesh sieve to obtain rape straw powder. Add deionized water to the rape straw powder at a solid-liquid ratio of 10 g / L, increase the temperature to 65 ° C, stir at 330 rpm for 2 hours, pour out the deionized water and floating impurities, and place the rape straw powder in a 60 ° C oven to dry to constant weight to obtain pre-treated rape straw powder;

[0054] S2. Accurately weigh 10 g of the pretreated rape straw powder prepared in step S1 and place it in a reactor. Prepare 1 L of a 15% NaOH aqueous solution and add it to the reactor. After mixing evenly, transfer the reactor to a microwave reactor, adjust the microwave power to 350 W, adjust the temperature to 110 ° C, and adjust the stirring speed to 250 rpm. When the temperature rises to 110 ° C, keep the reaction warm for 15 minutes, wait for the reaction system to cool to room temperature, obtain the alkali-treated reactant, and set it aside. Accurately weigh NaClO 2 40g was dissolved in 1L deionized water, 40mL acetic acid was added, and the mixture was mixed to prepare a bleaching solution. The alkali-treated reactant was washed with the bleaching solution until it was neutral, and then filtered. The precipitate was placed in an oven and dried at 40°C to constant weight to obtain rapeseed cellulose;

[0055] S3, accurately weigh 10 mL of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and dissolve it in 100 mL of 85 vol% ethanol aqueous solution, add glacial acetic acid to adjust the pH of the solution to 4.5, stir it at 250 rpm for 2 h, add 4 g of rapeseed cellulose prepared in step S2 to the solution, stir it at 250 rpm for 20 h at room temperature, centrifuge it at 5000 rpm for 20 min, remove the supernatant, wash the precipitate repeatedly with anhydrous ethanol to remove unreacted γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and dry it under vacuum at 60 ° C for 12 h to obtain modified rapeseed cellulose;

[0056] S4, accurately weigh 3 g of the modified rapeseed cellulose prepared in step S3, add 200 mL, 50 vol% methanol aqueous solution, mix well, adjust the solution pH to 9.5, increase the reaction temperature to 70°C, place on a magnetic stirrer and stir thoroughly at 200 rpm, after the temperature of the reaction system is uniform, add 1 mL of tetraethylene pentamine dropwise, continue stirring and reacting for 6 hours, stop heating, after the reaction system is cooled to room temperature, add 4 mL of methyl acrylate, continue stirring and reacting for 14 hours, continue to add 2 mL of ethylenediamine and stir and react for 1 hour, perform end-capping, remove the reaction solvent and excess reactants by vacuum distillation, wash repeatedly with deionized water and anhydrous ethanol, and vacuum dry at 50°C for 8 hours to obtain polyamine biocellulose;

[0057] S5. Accurately weigh 1 g of the polyamined rape cellulose prepared in step S4, add 25 mL of DMF solvent to fully dissolve the polyamined rape cellulose, introduce flowing nitrogen into the reaction system, add 1 g of potassium persulfate to fully dissolve it in the reaction system, add 5.4 mL of diallyldimethylammonium chloride aqueous solution (65 wt%), raise the reaction temperature to 75 ° C, react for 7 hours, wait for the reaction to cool to room temperature, precipitate with 100 mL of anhydrous ethanol, centrifuge at 4000 rpm for 5 minutes, collect the precipitate, wash it repeatedly with anhydrous ethanol and deionized water alternately for 3 times, and dry it in a vacuum drying oven at 40 ° C for 5 hours to obtain a modified reinforced composite fiber material;

[0058] The present invention also provides a modified reinforced composite fiber material for fracturing prepared according to the preparation method.

[0059] Comparative Example 1

[0060] This comparative example provides a composite fiber material and a preparation method thereof, which is different from Example 1 only in that the preparation method of the composite fiber material does not include step S5, and the remaining components, component contents and preparation method are the same as those of Example 1.

[0061] Comparative Example 2

[0062] This comparative example provides a composite fiber material and a preparation method thereof, which is different from Example 1 only in that the preparation method of the composite fiber material does not include step S4, and the remaining components, component contents and preparation method are the same as those of Example 1.

[0063] Experimental Example 1

[0064] In this experimental example, the structure of the composite fiber material prepared in Example 1 was measured. The composite fiber material prepared in Example 1 was analyzed using a Nicolet is10 Fourier transform infrared spectrometer. The potassium bromide tablet method was used for testing. The scanning beam range was 4000-500 cm -1 ;

[0065] Figure 1 This is the infrared spectrum image of the composite fiber material prepared in Experimental Example 1. As shown in the figure, at 3400-3350cm -1 A broad absorption peak appears at 2950-2890cm, which is the overlap of the stretching vibration peaks of NH and OH. -1 The stretching vibration peak of CH is at 1650-1620cm -1 -CONH 2 The stretching vibration peak of indicates that the composite fiber material described in Example 1 was successfully synthesized.

[0066] Experimental Example 2

[0067] In this experimental example, the microscopic morphology of the composite fiber material prepared in Example 1 was observed. The composite fiber material prepared in Example 1 was dispersed in deionized water at 5 wt %. After freeze drying, the microstructure was observed at room temperature (25° C.) using a Quanta 450 scanning electron microscope.

[0068] Figure 2 This is a SEM image of the composite fiber material prepared in Example 1 of the present invention. As shown in the figure, the composite fiber material prepared in Example 1 has a complex inter-crosslinked network structure, which is beneficial to improving the supporting performance and thickening performance of the composite fiber material for the fracturing fluid.

[0069] Application Example 1

[0070] The composite fiber materials prepared in Examples 1-3 and Comparative Examples 1-2 were added to tap water at an addition amount of 0.5 wt %, and 3 g of lignite, 1.5 g of a polymer flocculant (commercially available) and 0.8 g of NaOH were added to prepare a 1 L water-based drilling fluid system, which was placed on a high-speed stirrer and stirred at a speed of 1000 rpm for 1 h to prepare a water-based drilling fluid;

[0071] The water-based drilling fluid made of the composite fiber material described in Examples 1-3 and Comparative Examples 1-2 was placed on a Mars III rheometer to measure the steady-state rheological properties at room temperature; Figure 3 The steady-state rheological properties of the water-based drilling fluid made of the composite fiber material of Examples 1-3 and Comparative Examples 1-2 of the present invention are shown in the figure. During the operation of the drilling fluid, at a low shear rate, the drilling fluid maintains a high viscosity to facilitate the suspension of drill cuttings. At a high shear rate, the drilling fluid maintains a low viscosity to facilitate the reduction of resistance. Figure 3 In the examples, the drilling fluid prepared by the composite fiber materials prepared in Examples 1-3 can maintain good rheological adaptability and can effectively improve the thickening ability and adaptability of the drilling fluid; the composite fiber material of the present invention uses biocellulose, polyamine polymers and crosslinking agents to form a complex network structure, which can improve the thickening performance of the drilling fluid through the stability of the crosslinking structure, while maintaining the filtration performance, thereby improving the performance and work efficiency of the drilling fluid; the composite fiber material prepared in Comparative Example 1 lacks diallyldimethylammonium chloride, which contains a terminal olefin structure, and the polyamined biocellulose can undergo a crosslinking reaction with the double bond structure through the amine group, thereby further complicating the three-dimensional structure, while Comparative Example 2 lacks the crosslinked main body, the polyamine polymer, and although the terminal epoxy group in the modified biocellulose can also undergo a crosslinking reaction with diallyldimethylammonium chloride, its viscoelasticity is significantly reduced, and the resistance at high shear rate is relatively high.

[0072] Application Example 2

[0073] According to Application Example 1, the composite fiber materials prepared in Examples 1-3 and Comparative Examples 1-2 were prepared into drilling fluids, NaCl was added to the drilling fluids at a concentration of 20 wt%, and according to the API measurement standard, filter paper with a diameter of 90 mm was used to measure the filtration loss of the drilling fluids corresponding to Examples 1-3 and Comparative Examples 1-2 without NaCl and at a concentration of 20 wt%;

[0074] Figure 4 The results of salt resistance filtration loss of the composite fiber materials prepared by Examples 1-3 and Comparative Examples 1-3 are shown. As shown in the figure, the filtration loss of the composite fiber materials prepared by Examples 1-2 is not much different when the NaCl concentration is 0wt% and 20wt%, while Comparative Example 1 lacks a large amount of quaternary ammonium ions, resulting in poor salt resistance.

[0075] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

[0076] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a modified reinforced composite fiber material for fracturing, characterized in that: The specific steps include: S1. Place the biostraw in an oven, dry at 40°C to constant weight, place in a steel mill to crush, pass through a 200-mesh sieve, soak in deionized water, raise the temperature to 60-70°C, stir at 300-350rpm for 2-3h, place in an oven at 60°C to dry to constant weight, and obtain pretreated biostraw powder; S2, placing the pretreated bio-straw powder prepared in step S1 in a NaOH aqueous solution, transferring it to a microwave reactor, adjusting the microwave power to 300-400 W, adjusting the temperature to 100-110° C., adjusting the stirring speed to 200-250 rpm, and the reaction time to 15-25 min. After the reaction is completed, cooling, washing with a rinsing solution until neutral, placing in an oven and drying at 40° C. to constant weight, to obtain bio-cellulose; S3, dissolving γ-(2,3-epoxypropoxy)propyltrimethoxysilane in an ethanol aqueous solution, adjusting the pH to 4-4.5, adding the biocellulose prepared in step S2 according to the mass volume ratio of biocellulose to γ-(2,3-epoxypropoxy)propyltrimethoxysilane of 0.25-0.5 g / mL, placing at room temperature, stirring at 250 rpm for 20-24 hours, centrifuging at 5000 rpm for 10-20 minutes, removing the supernatant, washing the precipitate with anhydrous ethanol, and vacuum drying to obtain modified biocellulose; S4, dispersing the modified biocellulose prepared in step S3 in a 50% volume fraction methanol aqueous solution, mixing until uniformly dispersed, adjusting the pH to 9-9.5, raising the reaction temperature to 70-90°C, and after the temperature of the reaction system is uniform, adding tetraethylenepentamine dropwise according to a mass volume ratio of 2-4g / mL between the modified biocellulose and tetraethylenepentamine, stirring at a speed of 200rpm during the reaction, reacting for 4-6h, stopping heating, and after the reaction temperature is cooled to room temperature, adding methyl acrylate according to a volume ratio of 1:2-4 between tetraethylenepentamine and methyl acrylate, continuing to stir the reaction for 10-14h, adding ethylenediamine for end-capping, vacuum drying, removing the solvent and excess reactants, and obtaining polyamined biocellulose; S5. Dissolve the polyamined biocellulose prepared in step S4 in DMF, introduce flowing nitrogen, add potassium persulfate, add diallyldimethylammonium chloride in a mass ratio of polyamined biocellulose to diallyldimethylammonium chloride of 1:3-4, heat in a water bath to 70-80°C for reaction for 5-7h, cool after the reaction, add anhydrous ethanol for precipitation, centrifuge at 4000-5000 rpm for 3-5min, collect the precipitate, wash with anhydrous ethanol, and dry in a vacuum drying oven at 40°C to obtain a modified reinforced composite fiber material.

2. The method for preparing a modified reinforced composite fiber material for fracturing according to claim 1, characterized in that: In step S1, the biological straw includes at least one of wheat straw, corn straw, sorghum straw, rape straw, and sesame straw.

3. The method for preparing a modified reinforced composite fiber material for fracturing according to claim 2, characterized in that: In step S2, the mass concentration of the pretreated biostraw powder in the NaOH aqueous solution is 10-20 g / L; the mass fraction of NaOH in the NaOH aqueous solution in deionized water is 10%-20%.

4. The method for preparing a modified reinforced composite fiber material for fracturing according to claim 3, characterized in that: In step S2, the rinsing solution is a mixed aqueous solution of NaClO2 and acetic acid, wherein the concentration of NaClO2 in deionized water is 35-40 g / L; and the volume fraction of acetic acid in deionized water is 2%-4%.

5. The method for preparing a modified reinforced composite fiber material for fracturing according to claim 4, characterized in that: In step S3, the volume fraction of the γ-(2,3-epoxypropoxy)propyltrimethoxysilane in the ethanol aqueous solution is 5%-10%.

6. The method for preparing a modified reinforced composite fiber material for fracturing according to claim 5, characterized in that: In step S4, the mass concentration of the modified biocellulose in the methanol aqueous solution is 10-20 g / L; the volume ratio between the added volume of ethylenediamine and tetraethylenepentamine is 1.5-2:

1.

7. The method for preparing a modified reinforced composite fiber material for fracturing according to claim 6, characterized in that: In step S5, the mass concentration of the polyaminated bio-cellulose in DMF is 40-50 g / L; the mass ratio of potassium persulfate to polyaminated bio-cellulose is 1-2:

1.

8. A modified reinforced composite fiber material for fracturing, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Hyperbranched multiamino compound modified rice straw cellulose adsorbent and preparation method thereof

    CN107715846A

  • Reticular fibers for fracturing and preparation method thereof

    CN108660540A